Drivers of success in Somaliland's preschools: a predictive machine learning model of leadership commitment and institutional capacity - Ali, Jibril Abdikadir; Zeleke, Befekadu; Abdulahi, Bahir Adem; Golga, Dawit Negassa (Frontiers in Education, 2025)
This study develops a predictive machine learning model to identify the primary drivers of success in Somaliland's public preschools, conceptualized as institutional capacity. Early childhood education (ECE) is critical for development in post-conflict regions, yet there is a significant knowledge gap regarding the factors that foster institutional effectiveness in this context. Integrating Meyer and Allen's three-component model of commitment with the Resource-Based View of organizations, this research investigates how leadership commitment—specifically normative, affective, and continuance commitment—predicts the institutional capacity of preschools. A quantitative, cross-sectional survey design was employed, using a census sample of 129 educators and head teachers from all 33 public preschools across Somaliland. After comparing five regression techniques, a Robust Regression model was selected for its superior performance and resilience to outliers (RMSE = 2.16). The final model demonstrated significant predictive power (Pseudo R2 = 0.432), revealing a distinct hierarchy of influence among the commitment dimensions. Normative commitment, or a leader's sense of duty, emerged as the most potent predictor of institutional capacity (β = 0.63, p < 0.001). Affective commitment, reflecting emotional attachment, was also a strong positive predictor (β = 0.27, p < 0.001). In contrast, continuance commitment, based on the perceived costs of leaving, had a statistically significant but practically negligible impact (β = 0.04, p = 0.001). These findings indicate that in Somaliland's fragile context, a leader's dedication is driven by professional obligation and purpose rather than transactional incentives. The study makes a key methodological contribution by applying predictive analytics to educational leadership research, offering a nuanced and data-driven framework. The results provide an evidence-based blueprint for policymakers to design targeted interventions—such as professionalizing leadership roles and fostering peer support networks—to build a resilient and effective ECE system in Somaliland and other fragile settings.